Impact of Process and Product Modularity on Competitive Performance of Thailand manufacturing firms: Mediating role of Supply Chain Quality Integration - Kittisak Jermsittiparsert; Watcharin Joemsittiprasert; Muhamad Syazali (International Journal of Supply Chain Management, 2019)
This study empirically investigates the relation between modularity and the impact it has on competitive performance of firms. It focuses on both the dimensions of modularity including process and product modularity. With the vast development of supply chain integration in firms, this study focuses on the quality management perspective of firms by assimilating supply chain integration system with it. Supply chain quality integration system has attained a significant attention over the world that allow firms to strategically collaborate its external and internal supply chain processes in order to obtain high level quality and competitive performance. Using survey method, this study construct a questionnaire to collect data from the manufacturing firms of Thailand. The data collected from those firms in the form of 304 respondents is analyzed by using statistical tools including SPSS and AMOS by running various tests such as descriptive statistics, reliability tests, CFA and SEM to identify the theoretical relationships between variables. The results of this study clearly depicts that both process and product modularity signifies a positive association with competitive performance of firms. It also signifies the mediation impact of supply chain quality integration between modularity and performance. It means that integrated supply chain practices enhance the development of better quality and innovative products. It also help firms in improving their set up processes by reducing costs and delivery timings to the end users that effectively influence competitive strategies.